The institutional pre-conditions for regional labour market policy making in the EU: Case Studies and Policy Conclusions - Peter Huber (WWWforEurope, 2014)
Based on questionnaires conducted among PES organizations as well as Pacts and LEIs (Pacts/LEIs) in 40 cities of 12 EU member states and 2 non-EU member states – we take stock of the preconditions for conducting local labour market policies in an urban context in Europe and analyse the development of both regional PES organisations as well as Pacts/LEIs in the time since the economic crisis of 2008. Our findings suggest that the most effective measures to foster partnership based regional labour market approaches in the EU would consist of: a.) Increasing budgetary autonomy of the regional level of labour market policy institutions and aligning their competencies in other fields of labour market policy to the results that are expected from them, b) Investing in the development of partnership based policy institutions such as territorial employment pacts of local employment initiatives both in terms of the number of actors and their structure, d) Increasing the problem solution capabilities of regional actors by providing additional information in terms of evaluation and monitoring results with respect to policy measures and the regional labour market situation. In addition, the European Commission should on the one hand aim to raise awareness among national and regional policy makers on the benefits of decentralisation and devolution for regional labour market policy and to provide know-how and potentially also tools, sufficiently flexible to accommodate for the potentially widely varying needs of different local initiatives, for data generation, monitoring and evaluation. National governments, by contrast, should on the one hand aim to improve the vertical co-ordination of regional labour market policies by using best practice management tools of new public management in PES organisations and take an active role as a partner in Pacts/LEIs. They should also align the vertical distribution of formal competencies for labour market policy making in their respective countries with the tasks of (and the results expected from) regional policy organisations. From the perspective of the regional organisations, in particular this last point seems to be of major importance, since it is also considered to be the most important impediment to effective regional labour market policy making by them.
Keywords: J68; R23; 330; Academic research; challenges for welfare system; European governance; full employment growth path; good governance; high road strategy; institutional reforms; labour market policy; labour markets; local employment initiatives; multi-level governance; policy options; public employment services; socio-ecological transition; welfare state